DIFERENSIASI PROSES DALAM PEMBELAJARAN PUISI KELAS VII - Widia Siska; Sri Suciati; Ika Septiana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
21st century education with the Independent Curriculum requires educators to become adaptive and creative facilitators. However, until now the existing learning is still centered on educators and is cognitive in nature, so that Teaching and Learning Activities (KBM) limit students' creativity. Differentiated learning is a learning strategy that provides flexibility for students' interests, learning styles, and ability levels. This study aims to optimize student learning equality through the application of product differentiation learning at SMPN 39 Semarang. This study uses a qualitative descriptive approach. Data collection techniques are observation, interviews and documentation. Data analysis uses data condensation, data presentation, and drawing conclusions, data validity uses data and source triangulation. The results of the study show that the application of product differentiation at SMPN 39 Semarang is able to foster student creativity, as seen from the enthusiasm for learning, the products produced, imagination in implementing product making, participation in discussions, and initiative in expressing ideas. So that through product differentiation students get relevant and meaningful learning experiences.